Study of morbidity and mortality profile in special care newborn unit at tertiary care teaching institute in Vadodara, Gujarat, India - Pandya, Nimisha K.; Mehta, Kedar G. (International Journal of Contemporary Pediatrics, 2018)
Background: The development of a country is defined by its healthcare status especially the maternal and child health. Neonatal Mortality Rate in India has always been an area of concern again due to logistic issues in implementation of preventive and curative programs in a large and diverse country as ours but has shown a slow but steady fall in the last 2 decades. The current NMR of Gujarat is 25.4/ 1000 live births (2016) which is similar to the national NMR. The goal is to bring down NMR to single digit. Several measures are being taken to address these goals. The objective is to study the morbidity and mortality profile of newborns admitted to the Special Newborn Care Unit at GMERS Medical College and Hospital, Gotri, Vadodara between January 2017 and December 2017. Methods: Retrospective study was carried out at the Special Newborn Care Unit (SNCU), Department of Pediatrics, GMERS Medical College admitted in the period between January 2017 to December 2017. Both inborn and out born admissions were included. Newborns admitted in SCNU were analyzed for causes of morbidity and mortality. Results: 1039 neonates were admitted over a period of 1 year. The gender distribution was 1.5:1 (M: F). 54% admissions were out born. 62% were Low Birth Weight out of which 14% were term SFD vs.86% were premature. Majority of admission in SNCU were Neonatal hyperbilirubinemia 38%, followed by Sepsis in 23%, RDS in 16%, Perinatal asphyxia 15%. Congenital anomalies were reported in 3% newborns. The outcome rates for Survival, LAMA and death were 75%, 06% and 19%. The most common cause for mortality was sepsis (40%) followed by birth asphyxia (21.4%) and RDS (12.2%). Conclusions: The leading cause of morbidity were Sepsis, Birth asphyxia, Respiratory Distress Syndrome and prematurity. Sepsis was the leading causes of mortality in present study followed by Birth asphyxia and RDS. Leading causes of mortality in the study are preventable and curable. Therefore, surveillance and training interventions aimed at management of these causes should be established and strengthened.